2004
DOI: 10.1016/j.jhsb.2003.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Stopping Warfarin Therapy is Unnecessary for Hand Surgery

Abstract: Interruption of appropriate therapeutic warfarin therapy imposes a risk of morbidity and mortality on the patient. Strategies to reduce the risks of interruption impose relatively large costs in terms of prolonged hospital stay, medication and coagulation monitoring. We report a series of 47 consecutive surgical episodes on the hands of 39 patients without interruption of therapeutic warfarin anticoagulation and with an INR of between 1.3 and 2.9. There was no difficulty with intraoperative haemostasis. Two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 29 publications
1
32
0
3
Order By: Relevance
“…What has become apparent, however, is that the risk of bleeding is dependent on the nature of the procedure being performed [23]. Whilst warfarin need not be discontinued for elective hand surgery, most authors conclude that major surgery can only be performed if the INR is < 1.5 [24][25][26]. About 35% of the respondents in our study would, however, consider hemiarthroplasty with an INR > 1.5 and < 2.0.…”
Section: Discussionmentioning
confidence: 70%
“…What has become apparent, however, is that the risk of bleeding is dependent on the nature of the procedure being performed [23]. Whilst warfarin need not be discontinued for elective hand surgery, most authors conclude that major surgery can only be performed if the INR is < 1.5 [24][25][26]. About 35% of the respondents in our study would, however, consider hemiarthroplasty with an INR > 1.5 and < 2.0.…”
Section: Discussionmentioning
confidence: 70%
“…ACCP guidelines consider that it is safe to perform dental procedures in the presence of a therapeutic INR (1B) protecting against hemostasis by means of fibrinolysis inhibitors. Similar recom- (30). Considering patients on warfarin therapy (INR ranging between 2.0 and 3.0) normalization of the above-mentioned is observed after 4-5 days of discontinuation (31).…”
Section: Oral Anticoagulants -Vitamin K Antimetabolites (Vka)mentioning
confidence: 57%
“…In another retrospective study of patients undergoing hand surgery, Wallace et al reported only two of 39 patients experienced minor bleeding-related complications, neither of whom required reoperation [34].…”
Section: Discussionmentioning
confidence: 99%
“…One study suggests there is a greater risk of DVT or PE when oral anticoagulation is manipulated compared with the background risk without anticoagulation [3]. In addition to the loss of DVT and PE protection caused by perioperative manipulation of the anticoagulation regimen the patient is normally on, restoring the patient to their preoperative steady-state INR is associated with added costs [34].…”
Section: Discussionmentioning
confidence: 99%